Personalidade e sua relação com transtornos de ansiedade e de humor: Uma análise da produção científica brasileira na abordagem cognitivo-comportamental - Martins, Pablo Fernando Souza (2010)
Personality is one of the most controversial and intriguing theme in Psychology. In a general way, it could be understood as a set of rigid patters of feelings, thoughts, and behaviors from an individual. The aim of this investigation was describe how Brazilian researches in Psychology that use cognitive, behavioral, and cognitive-behavioral therapy referential have been approaching the subject Personality in their work. We also intended to determine the frequency of publications on Personality Disorders to compare this data with the bibliographical production on Anxiety and Mood Disorders. Moreover, we tried to describe how the Personality construct - and even Personality Disorders construct - has been addressed in the work on the Anxiety and Mood Disorders chosen for this review. The PePSIC Periódicos Eletrônicos em Psicologia - e SciELO.ORG - Scientific Electronic Library Online - databases were used for research. We investigated 53 journals, including two specific Cognitive Therapies and Behavioral-Cognitive Therapy (TCC) periodicals. Within each journal, we undertook a systematic survey on publications on the themes: Personality, Personality Disorder, Panic Disorder, Social Phobia, Obsessive-Compulsive Disorder (OCD), Generalized Anxiety Disorder, Major Depression, Dysthymia and Bipolar Disorder. A preliminary research has resulted in 218 articles. A second filter has obtained 81 articles in which we the focused on this review. There were found thirty-eight articles on Anxiety Disorders, twenty-five on Mood Disorders and eighteen on Personality Disorders. It was found that 90% of the papers on Anxiety Disorders make no reference to the term Personality or make it in a discrete way. This number rises to 96% to Personality Disorder group. Analyzing the specific journals on TCC we verified that 97% of the articles on Anxiety and Humor disorders do not cite the term Personality or cite but not explore it. This results point to the low rate of studies addressing the Personality and personality disturbs. Then, we can suggest that the difficulty on treating this Axis II disturbs has been worsened by lack of knowledge produced on the subject, either for lack of interest among researchers or because of the methodological obstacles found on this field.